Hemidesmosome integrity protects the colon against colitis and colorectal cancer. Issue 10 (1st July 2016) - De Arcangelis, Adèle; Hamade, Hussein; Alpy, Fabien; Normand, Sylvain; Bruyère, Emilie; Lefebvre, Olivier; Méchine-Neuville, Agnès; Siebert, Stéphanie; Pfister, Véronique; Lepage, Patricia; Laquerriere, Patrice; Dembele, Doulaye; et al.
Abstract : Objective: Epidemiological and clinical data indicate that patients suffering from IBD with long-standing colitis display a higher risk to develop colorectal high-grade dysplasia. Whereas carcinoma invasion and metastasis rely on basement membrane (BM) disruption, experimental evidence is lacking regarding the potential contribution of epithelial cell/BM anchorage on inflammation onset and subsequent neoplastic transformation of inflammatory lesions. Herein, we analyse the role of the α6β4 integrin receptor found in hemidesmosomes that attach intestinal epithelial cells (IECs) to the laminin-containing BM. Design: We developed new mouse models inducing IEC-specific ablation of α6 integrin either during development (α6 ΔIEC ) or in adults (α6 ΔIEC-TAM ). Results: Strikingly, all α6 ΔIEC mutant mice spontaneously developed long-standing colitis, which degenerated overtime into infiltrating adenocarcinoma. The sequence of events leading to disease onset entails hemidesmosome disruption, BM detachment, IL-18 overproduction by IECs, hyperplasia and enhanced intestinal permeability. Likewise, IEC-specific ablation of α6 integrin induced in adult mice (α6 ΔIEC-TAM ) resulted in fully penetrant colitis and tumour progression. Whereas broad-spectrum antibiotic treatment lowered tissue pathology and IL-1β secretion from infiltrating myeloid cells, it failed to reduce Th1 and Th17 response. Interestingly, while the initial intestinal inflammation occurred independently of the adaptive immune system, tumourigenesis required B and T lymphocyte activation. Conclusions: We provide for the first time evidence that loss of IECs/BM interactions triggered by hemidesmosome disruption initiates the development of inflammatory lesions that progress into high-grade dysplasia and carcinoma. Colorectal neoplasia in our mouse models resemble that seen in patients with IBD, making them highly attractive for discovering more efficient therapies.